Hardware modeling of binary coded decimal adder in field programmable gate array - Ibrahimy, Muhammad Ibn; Ahsan, Md. Rezwanul; Soeroso, Iksannurazmi Bambang (Science Publications, 2013)
There are insignificant relevant research works available which are involved with the Field Programmable Gate Array (FPGA) based hardware implementation of Binary Coded Decimal (BCD) adder. This is because, the FPGA based hardware realization is quiet new and still developing field of research. The article illustrates the design and hardware modeling of a BCD adder. Among the types of adders, Carry Look Ahead (CLA) and Ripple Carry (RC) adder have been studied, designed and compared in terms of area consumption and time requirement. The simulation results show that the CLA adder performs faster with optimized area consumption. Verilog Hardware Description Language (HDL) is used for designing the model with the help of Altera Quartus II Electronic Design Automation (EDA) tool. EDA synthesis tools make it easy to develop an HDL model and which can be synthesized into target-specific architectures. Whereas, the HDL based modeling provides shorter development phases with continuous testing and verification of the system performance and behavior. After successful functional and timing simulations of the CLA based BCD adder, the design has been downloaded to physical FPGA device. For FPGA implementation, the Altera DE2 board has been used which contains Altera Cyclone II 2C35 FPGA device.